Website Rekomendasi Anime Dengan Menggunakan Pendekatan Content-Based Filtering Berdasarkan Sinopsis - Suhendra, Arfal Razya; Putra, ST., M.Cs, I Gusti Ngurah Anom Cahyadi (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p54, 2022)
Today there are various kinds of Anime titles that can be found to be able to provide appropriate recommendations to Anime fans. A recommendation system is designed that can provide recommendations for Anime titles based on the similarity of the synopsis that has been read by users. The design of this Recommendation System uses a Content Based Filtering approach using the TFIDF method to obtain features that represent each synopsis which then produces a TFIDF matrix. The TFIDF matrix is then used as input to calculate the degree of similarity between synopsis. The results of the calculation of the degree of similarity become the basis for the formation of a function that can provide recommendations for Anime titles to users .